Structural Basis for the ABO Blood-Group Dependence of Plasmodium falciparum Rosetting - Vigan-Womas, Inès (Public Library of Science, 2012)
The ABO blood group influences susceptibility to severe Plasmodium falciparum malaria. Recent evidence indicates that the protective effect of group O operates by virtue of reduced rosetting of infected red blood cells (iRBCs) with uninfected RBCs. Rosetting is mediated by a subgroup of PfEMP1 adhesins, with RBC binding being assigned to the N-terminal DBL1α(1) domain. Here, we identify the ABO blood group as the main receptor for VarO rosetting, with a marked preference for group A over group B, which in turn is preferred to group O RBCs. We show that recombinant NTS-DBL1α(1) and NTS-DBL1α(1)-CIDR1γ reproduce the VarO-iRBC blood group preference and document direct binding to blood group trisaccharides by surface plasmon resonance. More detailed RBC subgroup analysis showed preferred binding to group A(1), weaker binding to groups A(2) and B, and least binding to groups A(x) and O. The 2.8 Å resolution crystal structure of the PfEMP1-VarO Head region, NTS-DBL1α(1)-CIDR1γ, reveals extensive contacts between the DBL1α(1) and CIDR1γ and shows that the NTS-DBL1α(1) hinge region is essential for RBC binding. Computer docking of the blood group trisaccharides and subsequent site-directed mutagenesis localized the RBC-binding site to the face opposite to the heparin-binding site of NTS-DBLα(1). RBC binding involves residues that are conserved between rosette-forming PfEMP1 adhesins, opening novel opportunities for intervention against severe malaria. By deciphering the structural basis of blood group preferences in rosetting, we provide a link between ABO blood grouppolymorphisms and rosette-forming adhesins, consistent with the selective role of falciparum malaria on human genetic makeup.